HAZARD IDENTIFICATION AND RISK ASSESSMENT (HIRA) PADA PROSES FABRIKASI PLATE TANKI 42-T-501A PT PERTAMINA (PERSERO) RU VI BALONGAN - Aristy Yulanda Ambarani; Abdul Rohim Tualeka (Universitas Airlangga, 2016)
HIRA is a process to identify all risk factor in a company then attempt to quantify the risk and determine whether it is acceptable or not. This study aimed to identify and assess occupational risk in the fabrication plate process, tank 42-T-501A, at PT Pertamina (Persero) RU VI Balongan. It is an observational and a cross-sectional study based on research time. The object of this study focuses on PT Pertamina (Persero) RU VI Balongan’s fabrication plate, tank 42-T-501A, workers with a total population of 20 people plus 1 safety inspector. Primary data obtained through observations and interviews which afterward presented in the form of tables and diagrams to be analyzed descriptively. The result showed that there were 6 procedures with 24 potential hazards and 24 occupational risks in the fabrication process tank 42-T- 501A. Based on the result of risk assessment, there are 6 low risk hazards, 6 medium risk hazards, 11 high risk hazards, and 1 extreme risk hazard from the total of 24 hazards in the fabrication plate process tank 42-T-501A. Finally, this study concludes that the dominant risk in the fabrication plate process tank 42-T-501A is high risk (45%). Examples founded in high risk category are stricken by plate, light exposure of torch, fume exposure of torch, sparks of cutting torch, light exposure of welding, fume exposure of welding, sparks of welding, explosions of sandblasting tube and explosions of sandblasting hose.Keywords: hazard identification, risk assessment, fabrication plate